G251(P) Quality improvement in training: establishing a paediatric-CAMHS collaborative learning programme. (May 2019) - Coleman, C; Stein, K
Abstract : Introduction: Recent reports have suggested that nearly a quarter of girls aged 14 have self-harmed in the past year, and newspapers report a 'crisis in children's mental health'. 1 With paediatricians seeing many more mental health presentations and CAMHS services increasingly stretched, there is a growing need for closer working across disciplines. This was acknowledged by the RCPCH in 2016, who stated that they 'wished to see more integration between paediatric, primary care and mental health training'. Aim: To establish and evaluate a joint learning programme for Community Paediatric and CAMHS trainees. Method: A joint committee was set up by community paediatrics and CAMHS higher specialist trainees to organise regional training days, alongside opportunities to share in each other's clinical encounters. The paired trainees on the committee attended various clinics, ward rounds and referral meetings in each setting, and organised a programme of joint training days for their respective paediatric and CAMHS colleagues. The sessions focused on improving their understanding of common presentations which sit squarely between the two disciplines, such as deliberate self-harm, eating disorders, neurodevelopmental conditions and medically unexplained symptoms. Results: The collaborative training experiences enabled the trainees in both specialties to network and reflect upon curriculum competencies in paediatrics and mental health. Feedback surveys were returned from 13 of the 16 participants following the pilot day of the collaborative learning programme. 92% of the participants reported an increase in their confidence on the topics taught, while 100% participants surveyed indicated their desire to attend further collaborative training. Qualitative feedback was overwhelmingly positive, with comments such as: 'Excellent opportunity to meet others in a related specialty', 'Highly relevant topics, ' and 'More days like this please'. Conclusion: Our results show that both paediatric and CAMHS trainees felt that the joint learning programme yielded significant benefits. Future in Mind (2015) highlighted the need for improved integration 'across the physical and mental health interface'. This integration should start at the trainee level, to benefit both the next generation of our workforce and ultimately our patients, who are increasingly crossing the disciplines. Reference: The Children's Society: Annual Good Childhood Report 2018.